Understanding the Determinants of Suicidal Behaviours Among People in Southwest Nigeria - Segun Lakin Oderinde; Temitope Adejoke Oderinde (Baltic Journal of Sport and Health Sciences)
Suicide is a prominent cause of mortality worldwide, and it is happening at an alarming rate in Nigeria, especially among young people. It is estimated that 800,000 individuals commit suicide each year. Previous research has found a number of factors, such as mental illness, financial hardships, marital issues, and social pressures that lead to suicidal behaviour. The causes of suicidal behaviour in Southwest Nigeria, however, have received little attention. In this study, the causes of suicidal behaviour among people in southwest Nigeria are examined. The study uses a qualitative methodology and gathers its data from secondary sources such as academic journals, books, newspapers, theses, and dissertations. The data demonstrate that major risk factors for suicide behaviour in Southwest Nigeria included sadness, anxiety, and hopelessness. Significant factors in suicide behaviour included social pressure, relationship issues, and financial hardships. The report also emphasises the role that stigma around mental health conditions and a lack of access to quality medical care play in escalating suicidal conduct. In order to encourage economic growth and development, the article advises the supply of mental health resources, the development of awareness campaigns, the construction of psychological and emotional support groups, overcoming financial obstacles, and collaboration with private organisations. The prevalence of suicidal conduct in Southwest Nigeria would decrease with the use of these approaches.